Hesperidin Increases Cytotoxic Effect of 5-Fluorouracil on WiDr Cells - Gilang, Yurista; Hermawan, Adam; Fitriasari, Aditya; Jenie, Riris Istighfari (Indonesian Journal of Cancer Chemoprevention, 2012)
Therapy  of  colon  cancer  by  using  5-FU  often  causes  problems  of  resistance.  This encourages the development of co-chemotherapy agent. One of the compounds that could potentially be used as a co-chemotherapy agent  is hesperidin. This study was conducted to determine the cytotoxic effects of hesperidin, 5-FU and the combination of them, as well as apoptosis induction in colon cancer cells WiDr. Cytotoxic effect of hesperidin, 5-FU, and its combination were observed using MTT assay. Observation of apoptosis was done by double staining method using ethidium bromide-acridin orange. Until 48 hours incubation, hesperidin showed no cytotoxic effects. Cytotoxic effects of 5-FU was observed after 48 hours with the IC50 value of 422 µM. However, hesperidin improved the cytotoxic effects of 5-FU at 48 hour incubation.  Either  single  treatment  of  hesperidin  200µM  or  5-FU  1500  µM  did  not  trigger apoptosis, but combination of them led to the emergence of signs of apoptosis. Based on this study,it can be concluded thathesperidin is potential to be developed as a co-chemotherapy agent of 5-FU on colon cancer but still need further study on its molecular mechanisms.Keywords : hesperidin, 5-fluorouracil, WiDr cells, cytotoxic, apoptosis